The Emulsion Polymerization of Each of Vinyl Acetate and Butyl Acrylate Monomers Using bis (2-ethylhexyl) Maleate for Improving the Physicomechanical Properties of Paints and Adhesive Films - K. A. Shaffei; A. B. Moustafa; A. I. Hamed (International Journal of Polymer Science)
Improving the water sensitivity of polyvinyl acetate PVAc films as well as pressure sensitivity, adhesion and washability of polybutyl acrylate were achieved by using bis (2-ethylhexyl) maleate (BEHM). The emulsion polymerization kinetics of vinyl acetate and butyl acrylate in presence of BEHM was studied. The order of the polymerization reaction with respect to the BEHM in presence of each of vinyl acetate and butyl acrylate was studied. The physicomechanical properties of the polyvinyl acetate films and vinyl acetate-butyl acrylate copolymer films were studied in presence of BEHM and the obtained results were matched with those prepared in the presence of pluronic F 108 and showed superior values. The obtained mean average molecular weights were found to be smaller in presence of BEHM assuring the presence of chain transfer reaction.